Great Christian jurists in American history - Dreisbach, Daniel L.; Hall, Mark David (Cambridge studies in law and christianity, 2019)
From the early days of European settlement in North America, Christianity has had a profound impact on American law and culture. This volume profiles nineteen of America's most influential Christian jurists from the early colonial era to the present day. Anyone interested in American legal history and jurisprudence, the role Christianity has played throughout the nation's history, and the relationship between faith and law will enjoy this worthy and unique study. The jurists covered in this collection were pious men and women, but that does not mean they agreed on how faith should inform law. From Roger Williams and John Cotton to Antonin Scalia and Mary Ann Glendon, America's great Christian jurists have brought their faith to bear on the practice of law in different ways and to different effects.